PERAN GURU DALAM PENGEMBANGAN KURIKULUM PAI UNTUK PENGUATAN KARAKTER RELIGIUS PESERTA DIDIK DI SD NEGERI CEPIT - Hilmi Asrori; Wasith Achadi (STKIP Subang, 2026)
Islamic Religious Education (PAI) in elementary schools plays a vital role in shaping students’ religious character. Teachers function not only as instructors but also as curriculum designers, implementers, and evaluators who are responsible for instilling religious values in students’ daily lives. This study aims to describe the role of teachers in developing the PAI curriculum at SD Negeri Cepit, focusing on curriculum design strategies, classroom implementation, supporting and inhibiting factors, as well as the impact on students’ religious character. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation studies, and then analyzed using the Miles & Huberman interactive model. The findings reveal that PAI teachers actively integrate religious values into teaching materials, methods, and extracurricular activities. Supporting factors include principal support, the school’s religious culture, and parental involvement, while inhibiting factors involve limited time allocation and a lack of innovative teaching resources. The development of the PAI curriculum has proven to strengthen students’ religious character, reflected in their discipline in worship, honesty, responsibility, and tolerance.